Práticas interformativas e desenvolvimento profissional de professores de jovens e adultos - Bezerra, Edneide da Conceição (2005)
The docent formation has been instigating researchers who look for ways to better qualify teachers in a way they can form and reform their practice in class. The category we brought for investigation and discussion is the formation that happens in the school these teachers work. This paper aims to study the repercussion of an inter-formative practice for the professional development of teachers from EJA 1st segment. The empirical field for the study was Professor Emília Ramos State School in Natal-RN/Brazil where, since its creation in 1988, has been developing a practice of formation continued on services characterized as Procedure of Inter-formation. The study fits in the qualitative approach of educational research. In methodological terms, it is a study case. Also, we were inspired by some elements from life history since we work on the teachers experiences in the School. Methodological tools such as semi-structured interviews, analysis of documents and participant observation were used. We invited 07 (seven) teachers from the night period of the school to revisit their formation history as teachers from EJA, counting on by their narrations apprehending the contributions of this formation on their professional development. The results collected show the school grants privileges to inter-formative practices based on collective and pair work, as well as on the teacher s reflection about his/her own practice. The Inter-formative Practice that happens in the School has an action-reflection-action basis where the docent action is read under the light of the theoretical support that fundaments the School s Pedagogical Proposal. The results also highlight the relevance of the inter-formative practices on the teachers professional development. This practice contributes to the construction of knowledge and competences, as well as to the identity of the teacher from EJA. For all the teachers interviewed, the School s formation has been the most significant contribution to their development as a teacher from EJA. Despite of the limitations found on using this kind of approach, we hope our study that talks about a well-succeeded experience can contribute to the widening of this type of practice, increasing then, the chances of making the dream of having a democratic high quality public school, despite all the difficulties, come true